Isolation and N-terminal amino acid sequence of membrane-bound human HLA-A and HLA-B antigens. - Bridgen, J; Snary, D; Crumpton, M (1976)
Membrane-bound HLA-A and HLA-B antigens have been extensively purified in good yield. The sequences of the N-terminal 16 amino acids have been determined using about 1 nmol of protein eluted from polyacrylamide gel after electrophoresis in sodium dodecyl sulphate.